Study of Changes in Fatty Acids Contents (ω3, ω6) and Chemical Quality Indicators in Frozen (Scomber japonicus) from the Marine Waters of Tartus - Saad, Adib; Yassin, Moufid; Kara-Ali, Ahmad; Mohamad, Rana (Latakia University Journal -Biological Sciences Series, 2019)
The objective of this research was to determine the changes in fatty acids contents, and chemical quality indices in Scomber japonicus (one of the Syrian commercial marine fish species) during frozen storage at (-18 °C). Fish samples were randomly collected from landing sites along the coast of Tartus governorate and kept at (0-4) °C immediately after fishing. They were then transferred to the laboratory in less than an hour, and treated by special methods, and similar samples were frozen and stored at (-18°C). The edible muscles were analyzed of Fresh and frozen at consecutive time intervals: (0, 30, 60, 90, 120, 180) day. The results showed that Unsaturated fatty acids (UFA), ( EPA; C20:5 ω3) and (DHA; C22:6 ω3) acids were higher than Saturated fatty acids (SFA) in fresh samples, but after 120 day of frozen storage, this ratio reversed. The numbers expressing the value of (TBA), Peroxide value (PV), Free Fatty acids (FFA), and pH values, increased during frozen storage due to lipid oxidation. هدف البحث الحالي إلى تحديد التغيرات في محتوى الأحماض الدهنية ومؤشرات الجودة الكيميائية في لحم سمك السكمبري الشائع Scomber japonicus، الذي يعدّ أحد الأنواع السمكية البحرية السورية ذات الأهمية الاقتصادية أثناء التخزين بالتجميد على (-18) مْ، جٌمعت العينات السمكية بشكل عشوائي من مواقع الإنزال لشاطئ محافظة طرطوس ثم حٌفظت على درجات حرارة منخفضة (4-0) مْ بعد الصيد مباشرةً بانتظار نقلها إلى المخبر خلال أقل من ساعة، ومعاملتها بطرائق خاصة، ثم جمدّت وخزنت عينات مماثلة على (18-) مْ، وتم تحليل العضلات المأكولة فقط بالحالة الطازجة والمجمدة على فترات زمنية متتالية:(0، 30، 60، 90، 120، 180) يوماً من التجميد. أظهرت النتائج أن نسبة الأحماض الدهنية عدم التشبع (UFA)وبشكلٍ خاص محتواها من (EPA, C20:5, w3) . (w3 (DHA, C22:6, كانت أعلى من نسبة الأحماض الدهنية المشبعة(SFA) للعينات الطازجة، بينما لوحظ وجود معدل عكسي بنهاية مدة التجميد، زادت الأرقام المعبرة عن قيمة حامض الثيوباربتويريك(TBA) ، رقم البيروكسيد (PV)، الأحماض الدهنية الحرة (FFA)، رقم (pH) خلال مدة التجميد بسبب أكسدة الدهون.